Implementasi Penggunaan Tes Objektif Dalam Evaluasi Pembelajaran Pendidikan Agama Islam di SMPIT Ar-Risalah Sukoharjo - Kayla Azzahra; Silviana Diah Sukmawati; Aqiila Khairunisa Nur Aisyah; Nurul Latifatul Inayati (FAKULTAS TARBIYAH INSTITUT AGAMA ISLAM SULTAN MUHAMMAD SYAFIUDDIN SAMBAS, 2023)
This research aims to describe and analyze objective tests, short answers in which students are only asked to choose several answer options provided by the teacher. Each school carries out accurate tests in different ways. Researchers conducting this research aim to reveal how the objective tests used at SMPIT Ar-Risale Sukoharjo are implemented in the Final Semester Assessment (PAS). This research uses qualitative research using a case study type. The data source in this research is primarily Islamic Religious Education teachers. Secondary data sources in this research are books, research journals, supporting websites, and school documentation. Data collection techniques are interviews, observation, and documentation. The analysis results at SMPIT Ar-Risale Sukoharjo stated that several types of objective tests were used in implementing the Final Semester Assessment (PAS). However, the accurate tests carried out in the Final Semester Assessment (PAS) have a poor effect on students. This happened in line with the change in the curriculum from K13 to the Independent Curriculum, where PAI subjects have been included in the service, and the government has published the questions. Based on the results of this research, the researcher hopes that the selection of test types can be considered again in the Final Semester Assessment (PAS).